Scanning The Business Environment For Information: a Grounded Theory approach - Zita Correia; T.D. Wilson (Information Research: An International Electronic Journal)
This paper summarizes the principal findings of research that sought to provide a comprehensive understanding of the environmental scanning process. The methodology used was of major importance in obtaining data that are grounded largely in the personal experience of managers, but also in documentary evidence and in direct observation by the researcher. The purpose of the study was to investigate how managers in the Portuguese chemical industry scan their environment for information, what are the contextual factors that affect this activity, and also how managers' perceptions of environmental change affect the strategic change they implement.